2021
DOI: 10.1109/access.2021.3105296
|View full text |Cite
|
Sign up to set email alerts
|

A Trajectory-Driven 3D Non-Stationary mm-Wave MIMO Channel Model for a Single Moving Point Scatterer

Abstract: This paper proposes a new non-stationary three-dimensional (3D) channel model for a physical millimeter wave (mm-Wave) multiple-input multiple-output (MIMO) channel. This MIMO channel model is driven by the trajectory of a moving point scatterer, which allows us to investigate the impact of a single moving point scatterer on the propagation characteristics in an indoor environment. Starting from the time-variant (TV) channel transfer function, the temporal behavior of the proposed non-stationary channel model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, without any hardware or firmware alteration, there is no known optimal solution to effectively isolate the different RF MIMO channel links. The problem of interference in the Ancortek radar has also been reported by the authors of [37], where they have subtracted the spectrograms to alleviate the interference problem. The solution proposed in [37] is suboptimal and nonrobust; it works when the interference component is smaller than the subchannel's main component and fails when the interference component is of the order of the magnitude of the main component of the subchannel.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, without any hardware or firmware alteration, there is no known optimal solution to effectively isolate the different RF MIMO channel links. The problem of interference in the Ancortek radar has also been reported by the authors of [37], where they have subtracted the spectrograms to alleviate the interference problem. The solution proposed in [37] is suboptimal and nonrobust; it works when the interference component is smaller than the subchannel's main component and fails when the interference component is of the order of the magnitude of the main component of the subchannel.…”
Section: Introductionmentioning
confidence: 74%
“…The problem of interference in the Ancortek radar has also been reported by the authors of [37], where they have subtracted the spectrograms to alleviate the interference problem. The solution proposed in [37] is suboptimal and nonrobust; it works when the interference component is smaller than the subchannel's main component and fails when the interference component is of the order of the magnitude of the main component of the subchannel. Therefore, in this paper, we propose an optimal and robust solution that completely eradicates the problem of cross-channel interference.…”
Section: Introductionmentioning
confidence: 74%
“…(1) Case With a limited literature search, we found that the spatialtemporal nonstationary characteristics of the nontarget signal channel are very different from those of traditional nonstationary channel models. The existing studies on channel nonstationary characteristics assume the natural scattering characteristic [33] [34]. In contrast, in the RIS coexistence scenario, the nonstationarity of the nontarget signal channel is mainly caused by the unexpected abnormal tuning of the RIS.…”
Section: The Tuning Coefficient Matrixmentioning
confidence: 99%
“…The broadband tuning characteristics of a RIS are beneficial for wireless broadband communication and support multiple bands [25]. However, each element of a RIS can only be set with a single weighting coefficient at a time, and cannot be set with different weighting coefficients for different signals on different sub-bands within the frequency range tuned by the RIS [26]. The RIS with the tuning characteristic uses the same weighting coefficient matrix to tune all signals incident on it in a wider frequency band.…”
Section: Influences Of Ris Regulatory Constraintsmentioning
confidence: 99%